ANALISIS BIBLIOMETRIK AUDIT SUMBER DAYA MANUSIA MENGGUNAKAN VOSVIEWER DENGAN PUBLISH OR PERISH (POP) - Junillah Erdianti; Putri Wulandari; Laurencia Zennita; Dara Kesumadewi; Siti Rodiah (CV. Denasya Smart Publisher, 2025)
Human resource management is an important theme for the growth of organizations and companies, and many issues related to human resource management in order to maintain the smooth operation of the organization. The main objective of this study is to integrate mapping analysis techniques and the use of VOSviewer software to conduct a comprehensive bibliographic analysis of scientific literature related to human resource management audits. The research data were obtained using the Publish or Perish (PoP) application. The data collected were obtained from search results containing the keyword